Une analyse des récits de vie des migrants vénézuéliens au Brésil - Glaucia Lara; Maíra Sant’Ana (Itinéraires)
In this paper, we are interested in the study of the migratory flow of Venezuelans to Brazil. The report “Refuge in numbers” (CONARE) reveals that in 2018, 80,057 people applied for recognition of refugee status in Brazil, Venezuelans representing 77 % of this amount. In general, the migrants from Venezuela cross the border to the small town of Pacaraima in Roraima State, which has a population of 18,913 inhabitants. The serious economic and social impacts on the state and in particular on the city have led experts to point out the biggest migratory crisis in the history of Brazil. But do Venezuelans see themselves as a problem for the host country? How do they (re)present themselves in their speeches? Since little space is usually given for these individuals to textualize their life experiences, we will try to restore their speech space by examining, in the light of Global Semantics (Maingueneau 2005), four life stories of Venezuelan migrants currently living in Brazil, in order to apprehend their (discursive) representations of themselves, of others, of the world.